Characterization of Feces-Derived Bacterial Membrane Vesicles and the Impact of Their Origin on the Inflammatory Response - Kameli, Nader; Borman, Reitske; López-Iglesias, Carmen; Savelkoul, Paul; Stassen, Frank R.M. (Frontiers in Cellular and Infection Microbiology, 2021)
The human gastrointestinal tract harbors a diverse and complex microbiome, which interacts in a variety of ways with the host. There is compelling evidence that gut microbial dysbiosis, defined as an alteration of diversity and abundance in intestinal microbes, is an etiological factor in inflammatory bowel disease (IBD). Membrane vesicles (MVs), which are nano-sized particles released by bacteria, have been found to interact with the host and modulate the development and function of the immune system. As a result MVs have been suggested to play a critical role in both health and disease. In this study we developed a method to isolate, characterize and assess the immunoreactivity of heterogeneous populations of MVs from fecal samples (fMVs) of healthy volunteers. We successfully isolated 2*109-2*1010 particles/ml from 0.5 gram of feces by using a combination of ultrafiltration and size exclusion chromatography (SEC) from 10 fecal samples. Bead-based flowcytometry in combination with tunable resistive pulse sensing (TRPS) provided a reliable method for (semi-)quantitative determination of fMVs originating from both Gram-positive and Gram-negative bacteria, while transmission electron microscopy confirmed the presence of fMVs. Real time 16s PCR on bacterial cell fractions or isolated fMVs DNA of the most common phyla (Firmicutes, Bacteroidetes, Actinobacteria and Proteobacteria) revealed differences in the relative abundance between bacteria and the fMVs. Moreover, fMVs evoke the release of TNF-α by THP-1 cells in a dose-dependent matter. Also, a significant positive correlation was found between Actinobacteria/γ-Proteobacteria derived vesicles and the release of TNF-α. It has become increasingly clear that fMVs could provide an additional layer to the definition of homeostasis or dysbiosis of the microbiota. The current study supports their potential involvement in the intestinal homeostasis or inflammatory disorders and provides putative interesting incentives for future research.